Verbal communication for the ventilator‐dependent patient requiring an inflated tracheotomy tube cuff: A prospective, multicenter study on the Blom tracheotomy tube with speech inner cannula. Issue 4 (23rd April 2012) - Leder, Steven B.; Pauloski, Barbara R.; Rademaker, Alfred W.; Grammer, Tracy; Dikeman, Karen; Kazandjian, Marta; Mendes, Joseph; Logemann, Jeri A.
Abstract Background The purpose of this study was to present our findings on the impact of the Blom tracheotomy tube with speech inner cannula on voice production abilities and speech intelligibility scores of ventilator‐dependent patients requiring a fully inflated tracheotomy tube cuff. Methods Prospective single group case‐series design permitted consecutive accrual of 23 adult inpatients from acute care and rehabilitation settings. Maximum ambient room noise, voice intensity, phonation duration of vowel /a/, and speech intelligibility scores were determined over 3 sessions. Results All participants achieved audible voicing with the Blom tracheotomy tube. Voice intensity was significantly greater than ambient room noise by >10 dB SPL (p = .003). Speech intelligibility scores improved significantly from 80% to 85% (p = .03). Phonation duration averaged from 3.30 to 3.45 seconds. There were no significant changes in oxygen saturation (p > .05), and no significant complications occurred. Conclusion The Blom tracheotomy tube with speech inner cannula permitted individuals requiring mechanical ventilation with a fully inflated tracheotomy tube cuff to produce excellent speech intelligibility for verbal communication. © 2012 Wiley Periodicals, Inc. Head Neck, 2013